The Role of Islamic Religious Education Teachers in Integrating Islamic Values in North Balikpapan 018 State Elementary School - Aufa Hanifan Hadi; Iskandar Yusuf (al-Afkar, Journal For Islamic Studies, 2024)
Every aspect of life, especially religious values, is influenced by education. Personal values of students in schools vary because of environmental factors that can affect their religious values. Thus, the purpose of this article is to determine the role of teachers of Islamic Religious Education (PAI) in integrating islamic religious values into the curriculum of education in Elementary School 018 North of Balikpapan. Descriptive qualitative methods are used in this study. The data obtained from this study comes from observations, interviews with PAI teachers, scientific journal literature, and books. Data analysis uses data reduction, data display, and conclusion. Teachers in Islamic education at Elementary School 018 North of Balikpapan have an integral role in guiding students towards higher perfection through the understanding of spiritual and moral values. Then the integrated education in the Elementary 018 North of Balikpapan created a more meaningful and integrated learning experience for the students, enabling them to understand the phenomenon from different perspectives.This provides a deep insight into the implementation of the Integrated Learning Model in creating a more holistic and contextual learning environment at the elementary school level. And the last one is an overview of how in the state Elementary School 018, the general education and religion are integrated without conflict, creating harmony that reflects the values of the Qur'an and overcoming the dichotomy between the "religious" and "common" sciences.